Effect of volatile compounds produced by Bacillus strains on postharvest decay in citrus. - Arrebola-Díez, Eva María; Sivakumar, Dharini; Korsten, Lise (Elsevier, 2009)
The antifungal effects of volatile compounds produced by Bacillus strains; Bacillus subtilis PPCB001 or Bacillus amyloliquefaciens PPCB004 and antagonist combination (PPCB001 + PPCB004) against Penicillium digitatum Sacc., Penicillium italicum Wehmer and Penicillium crustosum Thom isolates were investigated in vitro and in vivo. The antagonists alone or in combination inhibited the radial mycelial growth of Penicillium spp. in vitro. Among the three Penicillium isolates tested P. crustosum showed 73.3% of mycelial growth inhibition in presence of PPCB004. The antifungal effects of volatiles increased with increasing time (days), and PPCB004 showed the highest inhibition of radial mycelial growth in P. crustosum on the 10th day. The EC50 was 2.5 105 CFU ml 1 for PPCB001; 9.45 106 CFU ml 1 for PPCB004 and 7.76 106 CFU ml 1 for PPCB001 + PPCB004. Antagonist PPCB004 incubated at 37 C for 24 h showed higher inhibitory effect on spore germination and germ tube elongation in P. crustosum than all other treatments. Although, PPCB001 produced a higher number of volatile compounds (21 different types) than PPC004 (8 different types), 3-hydroxy-2-butanone (acetoin) was the predominant ketone produced by both PPCB001 (45.98%) and PPCB004 (97.52%). Antagonist PPCB004 showed significant inhibition on decay incidence and severity in Valencia, inoculated with P. crustosum and held at 25 C for 12 days. The observations indicated that B. amyloliquefaciens PPCB004 to control P. crustosum in postharvest systems.
Política de acceso abierto tomada de: https://v2.sherpa.ac.uk/id/publication/11272
Keywords: Cítricos - Almacenamiento - Enfermedades y daños; Agentes de control biológico de plagas; Antagonists; Antifungal effects; Bacillus spp.; Volatile compound; Citrus